Composite-suffixed nouns with locative meaning new ukrainian language late XVII – early XXI c. (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2013)
The dynamics of word-types and subtypes composite-suffixed nouns description for a locative and supporting substantive and verbal fundamentals new Ukrainian language late XVII – early XXI c.
Keywords: composite; verbal base; substantive base; supporting base; motivating base